Promoting Clean and Healthy Living in Schools: A Pre-Experimental Study on Disease Prevention - Nurlina, Nurlina; Aslinda, Aslinda; Harmawati, Harmawati; Nadeeya A’yn Mohamad Nor; Nathratul Ayeshah Binti Zulkifli; Ratna Mahmud; Abdul Halim (Fakultas Kesehatan Masyarakat, Universitas Muhammadiyah Palu, 2026)
Introduction: Clean and Healthy Living Behavior (PHBS) includes practices such as handwashing with soap, maintaining personal and environmental hygiene, proper waste disposal, and consuming nutritious food. According to the World Health Organization (WHO, 2021), up to 60% of childhood diarrhea cases can be prevented through proper hand hygiene. The Indonesian Ministry of Health (2020) also reports that the PHBS program in schools significantly reduces the incidence of infectious diseases. This study aims to evaluate the effectiveness of a PHBS education program in promoting disease prevention and improving health behaviors among elementary school students. Methods: A pre-experimental design was used, involving 50 students from SDN Bawakaraeng III Makassar. Data were collected through pre- and post-intervention tests and observational checklists. The program, conducted over four days, with sessions on personal hygiene, environmental cleanliness, and healthy eating habits. Statistical analysis was performed using the Wilcoxon signed-rank test to compare pre- and post-test scores, and McNemar’s test was used to assess changes in students' health practices. Results: Pre-test results showed an average score of 65 (out of 100), while post-test results increased to an average score of 85, indicating a significant improvement of 20 points (p-value = 0.031) based on the Wilcoxon test. The improvement was greater among female students, with an average increase of 23 points, compared to male students, whose average increase was 17 points. Observations revealed that 50% of students did not know the correct handwashing steps before the intervention, which increased to 75% after the program. Additionally, students' adherence to PHBS practices improved significantly, rising from 50% to 70% (p-value = 0.013) as assessed by McNemar’s test. Conclusion: The findings demonstrate that the PHBS education program significantly improved students' awareness and practices regarding disease prevention, as evidenced by the measurable increases in knowledge and behavior change.